KETAHANAN KAYU BAKALA (Alstonia spectabilis) TERHADAP DEGRADASI MARINE BORERS : (Resistance of Bakala Wood (Alstonia spectabilis) To Degradation of Marine borers) - Niken Pujirahayu; Abigael Kabe; zakiah uslinawaty; Nurhayati Hadjar; Nurnaningsih Hamzah; Nur Swarziani; siiti sarina; wa ode Saraswati; Attar Muhammad (Jurusan Kehutanan -FHIL-UHO, 2024)
Alstonia spectabilis (Bakala) is a fast-growing tree species native to Southeast Sulawesi, Indonesia, with potential applications in maritime and coastal construction. Despite its promising economic value, Bakala wood is still limited in its use due to a lack of understanding of its physical properties and resistance to marine borers, which can cause significant damage to wood structures in marine environments. This study aims to evaluate the natural resistance of Bakala wood to marine borer attacks. Wood resistance testing was carried out by immersing wood samples in seawater for three months and assessing the damage caused. The results showed significant color changes and hole formation, with damage intensity varying in various parts of the wood. The tip and middle parts showed severe degradation, with damage intensity of 58.8-61.3%, classified as poor according to SNI 01-7207-2006 standards, while the base of the wood showed moderate damage with an average damage intensity of 50.1%. The identified marine borer species responsible for the damage include Teredo navalis (family Teredinidae), Lichenopora (genus bryozoan), and Martesia striata (family Pholadidae). These findings suggest that while Bakala wood has potential for use in coastal and marine applications, its poor resistance to marine borers means that further research into protective treatments or selective use in marine environments is needed.